Gender, Education and Citizenship as Ideological Weapons of an ‘Army of Holy Women’ in Bengal: The Matua Matri Sena - Sarbadhikary, Sukanya (Religions, 2023)
This paper seeks to analyze the recent phenomenon of the development of a Matri Sena (literally, an ‘Army of Holy Women’) among the Matua sect of West Bengal, India. Historically known to have suffered caste-based untouchability and forced migration due to communal conflict, the Matua community’s current political motivations surround the issue of ‘refugeehood’ and Indian citizenship. Given this background, the emergence of the Matri Sena as a complex identity among a religion–caste–gender–nation nexus is oriented towards bipartite objectives: one, to actualize the gender-egalitarian ethos that informs Matua religious foundations, and two, to claim legal citizenship status for its community members precisely through a new gendered ideology. We argue that the women gurus of the Matri Sena are able to realize their religious/political aims by fashioning themselves as mothers of an ideal family, community, and by extension, the nation. In deploying their specific gendered ideological constructions, they enact their new roles as influencers in both private and public Matua lives. In such renderings, the woman guru’s mother-figure emerges as a political subject through crucial engagements with Matua religiosity on one hand, and dominant Hindu nationalist discourses on the other. In this article, we critically analyze ways in which the Matri Sena constructs a new maternal notion of religio-political power, and how such power furthers both collective Matua aspirations and contemporary national imaginations.